Management of oral adverse effects related to cetuximab plus radiotherapy - Corrêa, Danilo da Silva; Oliveira, Thaís Feitosa Leitao de; Santos, Paulo Sérgio da Silva (Journal of Oral Diagnosis, 2017)
Squamous cell carcinomas of head and neck have an incidence of more than five hundred thousand cases a year worldwide. The standard treatment of this condition consists of platinum-based chemotherapy and radiotherapy. Nevertheless, in case of advanced age or reduced general condition the chemotherapy agent utilized is Cetuximab, a molecular targeted drug, used for metastatic colorectal cancer and head and neck cancer. Adverse effects associated with Cetuximab can be potentiated by the radiotherapy leading to oral mucositis and skin toxicities. We report a case of a 70-year-old caucasian woman who had removed a gingival squamous cell carcinoma at the left side of the mandible. During intensity modulated radiotherapy and Cetuximab chemotherapy she began to develop severe oral mucositis and perioral and neck skin toxicities. The pain associated with the oral mucositis prevented the patient from eating, causing a break in radio and chemotherapy. The treatment with systemic and topical medications and low-level lasertherapy was applied. The patient tolerated well the treatment and fifteen days after it began, radio and chemotherapy was reinitiated and concluded with no more adverse effects. It is important to the medical team to be aware of it, since the early identification and treatment of its signs and symptoms reduces the risks of breaks in the treatment and provides better quality of life to these patients.